Retinoid X receptor heterodimers in hepatic function: structural insights and therapeutic potential - Xu, Renjie; Zhang, Linyue; Pan, Hao; Zhang, Yong (Frontiers in Pharmacology, 2024)
Nuclear receptors(NRs) are key regulators of multiple physiological functions and pathological changes in the liver in response to a variety of extracellular signaling changes. Retinoid X receptor (RXR) is a special member of the NRs, which not only responds to cellular signaling independently, but also regulates multiple signaling pathways by forming heterodimers with various other NR. Therefore, RXR is widely involved in hepatic glucose metabolism, lipid metabolism, cholesterol metabolism and bile acid homeostasis as well as hepatic fibrosis. Specific activation of particular dimers regulating physiological and pathological processes may serve as important pharmacological targets. So here we describe the basic information and structural features of the RXR protein and its heterodimers, focusing on the role of RXR heterodimers in a number of physiological processes and pathological imbalances in the liver, to provide a theoretical basis for RXR as a promising drug target.